Rozbudowa i modernizacja infrastruktury transportowej jako narzędzie wzmacniania konkurencyjności regionów - Potoczna, Iwona (The Development and Modernization of Transportation Infrastructure as an Instrument of Strengthening Regions Competitiveness, 2006)
The development, modernization and social integration of regions is a condition of well developing infrastructure. The aim of the article is to describe how to accelerate qualitative changes of transportation infrastructure in terms of structural funds. These operations provide strengthening competition of regions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 123-132